The Influence of Working Hours, Workload, Incentives and Work Motivation on Performance of Employees at the National Land Agency of Labuhan Batu - Ahyar, Hajarul; Elvina, Elvina; Halim, Abd. (Budapest International Research and Critics University, 2022)
Human resources (HR) become the driving force for institutions to achieve goals with the work achieved. Efforts to develop this goal, the National Land Agency of Labuhanbatu Regency can implement working hour’s regulations, workload balance, incentives and motivation so that employee performance can be realized. This study aims to analyze the effect of working hours, workload, incentives and motivation on the performance of the employees of the National Land Agency Office of Labuhanbatu Regency. This type of research is quantitative with data collection techniques used are observation, documentation and questionnaires. The population in this study were 119 employees of the National Land Agency Office of Labuhanbatu Regency. The research sample was taken using the slovin formula, with a total of 92 people.The test results partially prove that the t arithmetic value is 2.020 > t table 1.6625, which means working hours (X1) have a positive effect on the employee performance variable (Y). Then the value of t arithmetic is 5.806 > t table 1.6625 explaining that workload (X2) has a positive effect on employee performance variable (Y). Furthermore, the results of the regression analysis with a t-count value of 2.090 > t-table 1.6625 proves that the incentive (X3) has a positive effect on the employee performance variable (Y). The results of the regression analysis of the t arithmetic value of 2.060 > t table 1.6625 explains that motivation (X4) has a positive effect on employee performance variables (Y). Simultaneous test analysis in this study shows that the value of Fcount is 23,803> Ftable 2.48 with a significance value of 0.000 <0.05. From these results,Working Hours (X1), Workload(X2), Incentives (X3) and Motivation (X4)positive and significant effect on employee performance (Y). The value of R Square from the analysis of the coefficient of determination of 0.523 means that work productivity can be explained by the variableWorking Hours (X1), Workload(X2), Incentives (X3) and Motivation (X4) by 52.3%, while the remaining 47.7% can be explained by other variables not examined in this study.